An axiomatic system engineering design method based on NSGA-II algorithm applied to complex systems - Zhang, Xiaoqian; Zhang, Qinghai; Zhao, Qingjian; Zhao, Shuang; Zhao, Yanan; Guo, Yang; Zhao, Zhengxu; Song, Liqiang (Scientific reports, 2025)
This study proposes an integrated framework that combines Axiomatic Design with Model-Based Systems Engineering, incorporating NSGA-II as an intelligent optimization engine. The framework constructs a multi-level traceability matrix linking requirements, functions, behaviors, and structural elements, and leverages NSGA-II to dynamically optimize the sequencing of the Design Structure Matrix, thereby enhancing the explicitness and visualization of coupling relationships. Rather than directly eliminating dependencies, the approach aims to support a more systematic modularity-oriented analysis. Implemented using SysML, the framework establishes formal mappings among the user, functional, behavioral, and physical domains to ensure bidirectional traceability. In parallel, coupling degrees are quantitatively assessed based on axiomatic design principles, and a multi-objective intelligent search is employed to accelerate convergence within large-scale design spaces. A case study on an active reflector control system demonstrates that the proposed NSGA-II–enhanced framework significantly reduces reliance on expert knowledge in DSM ordering, and exhibits clear advantages in coupling identification and modularity analysis for complex systems.